Obstetric and psychological factors as predictors of early postpartum anxiety - Nakić, Sandra (Array, 2010)
Even though previous studies have shown that maternal prenatal anxiety was associated with obstetrical problems, foetal development, behavioural problems of the newborn, and postpartum depression, not much attention was given to the postpartum anxiety. The aim of this study was to assess anxiety symptoms in new mothers and to establish which obstetrical and psychological factors contribute to state anxiety. Participants were 333 postpartum women. Inclusion was limited to mothers without any psychiatric disorder in the anamnesis, who gave birth to a child with Apgar score higher than 7. Croatian version of Spielberger State-Trait Anxiety Inventory (STAI), adapted version of Social Support Appraisals Scale (SS-A), Rosenberg Self-Esteem Scale (RSES) and the demographic information form were administered 2 days postpartum. Other relevant data were collected from medical documentation. Results have shown that 18% of women had anxiety score above cut-off. Women who were primiparas, who had caesarean section, had epidural anesthesia, and gave birth to a preterm baby, had higher anxiety scores. The hierarchical regression analysis has shown that trait anxiety was the strongest predictor of the state anxiety. Obstetric factors explained the additional variance, but other psychological variables did not contribute significantly to the state anxiety.